THE ONLINE ADVERTISING OF SMALL AND MEDIUM SIZED BUSINESSES - BĂLTEANU, Cristina; MARCU, Mihaela (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
The recent decades have brought a new concept, namely the digital communication, which allows information to travel at a much more rapid rate and promotional messages (video, audio or simple texts) to be perceived in real time in different parts of the world. In the online environment, interactivity is the key term, the user being the one who sets up an online profile according to which he gets personalized messages. Thus, the organizations can more easily interact with customers, allocating budgets much lower than those used for traditional media. Therefore, SMEs have a real opportunity to promote themselves in a more efficient manner, at low cost and globally, the Internet offering them the possibility of becoming known among consumers from other states than their home country. In this context, the paper's main objective was the analysis of online advertising market in Europe and also the identification of the main results arising from the implementation of the SMEs promotion campaigns in the virtual environment. The results showed the huge potential of the Internet in terms of online advertising and the main tools that can be used successfully in the efforts of attracting and making customers loyal.